2019
DOI: 10.1093/nc/niz006
|View full text |Cite
|
Sign up to set email alerts
|

A match does not make a sense: on the sufficiency of the comparator model for explaining the sense of agency

Abstract: The development of a sense of agency is indispensable for a cognitive entity (biological or artificial) to become a cognitive agent. In developmental psychology, researchers have taken inspiration from adult cognitive psychology and neuroscience literature and use the comparator model to assess the presence of a sense of agency in early infancy. Similarly, robotics researchers have taken components of the proposed mechanism in attempts to build a sense of agency into artificial systems. In this article, we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…In both the comparator and predictive processing accounts, agency is associated with small prediction error, or a match between expected and actual outcomes of actions. The comparator however focuses on net retrospective prediction error and cannot account for hypothesis switches in the face of accumulating prediction error or other changes in future action based on inferences of agency (see also Zaadnoordijk, Besold, and Hunnius (2019) ). The predictive processing account positions agency in a broader theory of action and policy selection.…”
Section: Discussionmentioning
confidence: 99%
“…In both the comparator and predictive processing accounts, agency is associated with small prediction error, or a match between expected and actual outcomes of actions. The comparator however focuses on net retrospective prediction error and cannot account for hypothesis switches in the face of accumulating prediction error or other changes in future action based on inferences of agency (see also Zaadnoordijk, Besold, and Hunnius (2019) ). The predictive processing account positions agency in a broader theory of action and policy selection.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, if no evidence supports the link between sense of agency and the goal-directed behavior of the organism, this account becomes a mentalist, adultist, and non-parsimonious interpretation of infant experience. The sense of agency in newborns cannot be justified by analogy with the adult experience, because infants may lack the necessary cognitive architecture for it (Zaadnoordijk et al, 2019). Further, by stating that sense of agency is intrinsic to any goal-directed action, the classical view proposes a black-box, preformist explanation of action awareness, which is insensitive to variations of the mental implementation of behavior also in the case of adults.…”
Section: A Causal View Of the Sense Of Agencymentioning
confidence: 99%
“…Empirical research has shown that a match is important between perceptual changes the agent aimed at prior to generating efferent activity (often called “goals”), and the actual perceptual feedback after the efferent activity had been emitted (for a recent overview, refer Haggard, 2017 ). If there is a match between goal and feedback, it is likely that this feedback was caused by the agent’s efferent activity ( Carruthers, 2012 ; Haggard and Chambon, 2012 ; Gallagher, 2013 ; Zaadnoordijk et al, 2019 ). If there is a mismatch, it is more likely that the postaction percept was caused by something else than efferent activity.…”
Section: Sense Of Agencymentioning
confidence: 99%